2020
DOI: 10.1088/1742-6596/1567/4/042049
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of blended project-based learning model on astronomy learning to increase critical thinking skills

Abstract: This study aims to analyse the critical thinking skills of prospective science teacher students during astronomy lectures by applying a Blended Project Based Learning model. This research is a type of descriptive research with a quantitative approach. The study population was all semester 4 science students of science at one of the state universities of educational staff in Central Java, Indonesia. Students’ critical thinking skills experience a very good change after working on the project. The results of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
6
0
2
Order By: Relevance
“…It has become a necessity now to give importance to critical thinking in the textbooks and to prepare the content of the textbooks in a way that will develop critical thinking (Öztürk & Razgatlıoğlu, 2013). The positive results of the studies in the literature that are taught based on activities and methods that will develop critical thinking in the field of astronomy (For example; Allen & Kelly-Riley, 2005;Costa & Johnson, 2020;Demirci & Özyürek, 2017;Ridlo, Dafik, & Nugroho, 2020;Taufiq, Wijayanti, & Yanitama, 2020). Today, it is known that the most used teaching material in the teaching-learning process by teachers is textbooks.…”
Section: Discussionmentioning
confidence: 99%
“…It has become a necessity now to give importance to critical thinking in the textbooks and to prepare the content of the textbooks in a way that will develop critical thinking (Öztürk & Razgatlıoğlu, 2013). The positive results of the studies in the literature that are taught based on activities and methods that will develop critical thinking in the field of astronomy (For example; Allen & Kelly-Riley, 2005;Costa & Johnson, 2020;Demirci & Özyürek, 2017;Ridlo, Dafik, & Nugroho, 2020;Taufiq, Wijayanti, & Yanitama, 2020). Today, it is known that the most used teaching material in the teaching-learning process by teachers is textbooks.…”
Section: Discussionmentioning
confidence: 99%
“…The case shows that projectbased blended learning is more effective to improve practical competences, independent study, curiosity, and teamwork motivation for students (Tong, Kinshuk, & Wei, 2020). Applying project-based blended learning can support critical thinking after doing a project (Taufiq et al, 2020).…”
Section: Figure 4 Histogram Of Improvement Of the Second Basic Competencementioning
confidence: 98%
“…Here is the evidence of the relevant researches about project-based blended learning. First, Taufiq, Wijayanti, & Yanitama, (2020) explained that the use of project-based blended learning for analyzing critical thinking competencies for candidates of science teachers in astronomy subjects integrated with Moodle LMS can improve the students' critical thinking after completing the project. Then, Nurbekova et al, (2020) showed that utilizing project-based blended learning has a big influence on IT students in developing mobile apps like project-based technology, programming, teamwork, and the use of digital for learning content.…”
Section: Introductionmentioning
confidence: 99%
“…Hasil temuan ini sejalan dengan penelitian sebelumnya yang membuktikan bahwa model pembelajaran berbasis proyek memberi pengaruh positif terhadap kemampuan berpikir kreatif siswa dalam pembelajaran IPA (Fiteriani et al, 2021;Hasibuan et al, 2022;Mamahit et al, 2020;Pramesti et al, 2022;Pratika Surya & Wahyudi, 2018;Putri et al, 2019;Saefullah et al, 2021;Saputri et al, 2022;Setiawan et al, 2021;Shalihah et al, 2020;Sukmawijaya et al, 2019;Taufiq et al, 2018;Viana et al, 2019;Waliyati et al, 2019;Widyasmah et al, 2020;Yamin et al, 2020). Pada pembelajaran berbasis proyek siswa perlu melakukan beberapa hal seperti menerima tantangan dari masalah, merencanakan strategi penyelesaian masalah, menerapkan strategi, dan menguji kembali solusi yang diperoleh.…”
Section: Hasil Dan Pembahasanunclassified